An Analysis of the Oxford Bilingual School Dictionary: Northern Sotho and English (De Schryver 2007) - Kosch, Inge (Lexikos, 2013)
The Oxford Bilingual School Dictionary: Northern Sotho and English (De Schryver 2007) is a welcome addition to dictionaries that have been compiled for school use in particular. Its novelty and appeal lie in the fact that the lemmas and Northern Sotho mini-grammar are based on a corpus of general language usage and school textbooks. It reflects current language usage and concerns in the modern world that learners can easily relate to, making it a popular alternative to the more traditional dictionaries. This bidirectional, bilingual dictionary is equally useful to native speakers of Northern Sotho learning English and to English-speakers acquiring Northern Sotho. Though the number of lemmas is restricted to 5 000 in the lemma lists for Northern Sotho and English respectively, the compilers nevertheless succeeded in meeting the basic lexicographic and grammatical needs of the learner. This review article aims to take a critical look at various features of the dictionary.